2009
DOI: 10.1002/14651858.cd006406.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow harvest versus peripheral stem cell collection for haemopoietic stem cell donation in healthy donors

Abstract: The different short-term morbidities associated with each type of haemopoietic stem cell donation were clear, with bone marrow donors experiencing more pain and more restriction post-donation than peripheral blood donors. However, the studies were limited by their methodological quality, failure to provide long-term follow up (for which larger numbers of donors would be required) and a failure to apply consistent measures of quality of life in a way which allows more meaningful evaluation across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Several studies are available comparing the outcome of HCT from an HLA-identical sibling wherein peripheral blood is the source of HPC with that following a BM harvest. [6][7][8][9][10][11][12] Over the last years, reduced intensity conditioning (RIC) has enriched the treatment possibilities for elderly patients whose disease could be cured with HCT. The frequencies of RIC HCT have risen from less than 1% of all allogeneic HCT in 1998 to 34% in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are available comparing the outcome of HCT from an HLA-identical sibling wherein peripheral blood is the source of HPC with that following a BM harvest. [6][7][8][9][10][11][12] Over the last years, reduced intensity conditioning (RIC) has enriched the treatment possibilities for elderly patients whose disease could be cured with HCT. The frequencies of RIC HCT have risen from less than 1% of all allogeneic HCT in 1998 to 34% in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Not all donors from the parent trials were included in some of the randomized studies, and the ability to draw strong conclusions based on these studies is limited by low numbers and methodological weaknesses. 14 This study is the first to prospectively compare the experiences of unrelated BM and PBSC donors using validated, high-quality instruments that give detailed understanding of what donors experience on a day-to-day basis through the donation process. The study includes nearly 9500 donors collected through a large network of donor/collection centers between 2004 and 2009 and therefore should be considered a standard for expected safety outcomes of unrelated donors.…”
mentioning
confidence: 99%
“…Significantly increased levels of G-CSF have also been described in the cecal and colonic contents of mice with C. difficile gastrointestinal infection [11]. Previous studies have demonstrated that administration of G-CSF in both mice and humans induces the mobilization of leukocytes, including hematopoietic stem cells, from the bone marrow into circulation; a process commonly used for the clinical transplantation of stem cells [12, 13]. Specifically, G-CSF stimulates the release of proteases (i.e., elastase, cathepsin G) from mature bone marrow PMNL resulting in the cleavage of VCAM-1 [12, 13] and CXCR4 [1416] which are key adhesins that regulate leukocyte egress from the hematopoietic compartment.…”
Section: Discussionmentioning
confidence: 99%